2016
DOI: 10.3389/fmicb.2016.02024
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR-Based Endometabolome Profiles of Burkholderia cenocepacia Clonal Variants Retrieved from a Cystic Fibrosis Patient during Chronic Infection

Abstract: During cystic fibrosis (CF) chronic lung infections, bacteria of the Burkholderia cepacia complex (Bcc) are exposed for several years to a stressful and changing environment. These environmental challenges results in genetic changes of the initial infecting strain with the consequent diversification of genotypes and phenotypes. The exploitation of functional and comparative genomic approaches has suggested that such diversification is associated with massive metabolic remodeling but these alterations are poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…NMR-based metabolomics has previously been used to investigate bacterial stress adaption in response to environmental stimuli or antimicrobial exposure (Hoerr et al, 2016). Taking a similar approach, we identified 45 metabolites in the cytoplasm of B. thailandensis which is comparable with a study that identified 25 metabolites in the cytoplasm of B. cenocepacia (Moreira et al, 2016). Our complementary data sets analyzing the proteome and metabolome of E555 treated cells will provide insight into the metabolic pathways affected by 12-bis-THA.…”
Section: Discussionsupporting
confidence: 65%
“…NMR-based metabolomics has previously been used to investigate bacterial stress adaption in response to environmental stimuli or antimicrobial exposure (Hoerr et al, 2016). Taking a similar approach, we identified 45 metabolites in the cytoplasm of B. thailandensis which is comparable with a study that identified 25 metabolites in the cytoplasm of B. cenocepacia (Moreira et al, 2016). Our complementary data sets analyzing the proteome and metabolome of E555 treated cells will provide insight into the metabolic pathways affected by 12-bis-THA.…”
Section: Discussionsupporting
confidence: 65%
“…This patient was also co-infected with B. multivorans , another member of the Bcc, which appeared before the isolation of the early B. cenocepacia strain (isolate IST439); co-infection continued until near the patient’s death ( Cunha et al, 2003 ). The B. cenocepacia isolates from this patient were characterized by phenotypic ( Coutinho et al, 2011a ), transcriptomic ( Mira et al, 2011 ), proteomic ( Madeira et al, 2011 , 2013 ) and metabolic profiling ( Moreira et al, 2016a ), as well as by comparative genomics (still unpublished). Isolates of particular interest are B. cenocepacia IST4113 (a highly antibiotic resistant variant retrieved after an exacerbation treated with intravenous therapy), IST4134 (obtained just before the patient’s death), and IST4129 (a variant that exhibits attenuated virulence related with the loss of the third replicon ( Moreira et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…These isolates were picked at random from selective agar plates obtained in the major Portuguese CF Center at Hospital de Santa Maria during consultation routines. The clinical isolates examined are of high interest in the context of this study because they were previously characterized by phenotypic 11 , transcriptomic 40 , proteomic 27,41 and metabolic profiling 42 . Results on the comparison of the virulence potential of these isolates using non-mammalian infection models and of their ability to modulate dendritic cell function are also available 25,43 .…”
Section: Introductionmentioning
confidence: 99%